Dynamic physical education for secondary school students - Brusseau, Timothy A. Jr; Darst, Paul W.; Pangrazi, Robert P.; Erwin, Heather 1979- (Human Kinetics, 2021)
"DPE emphasizes the skill development, activity promotion, and physical fitness behaviors that are the foundation of physical literacy. DPE advocates instructional practices designed to create a learning environment where students are free to experiment, learn, and experience physical activity in a positive climate. DPE goes beyond physical education classes by promoting physical activity throughout the school day and beyond"--